PENGARUH IKLIM KERJA, KEPUASAN KERJA, DISIPLIN KERJA TERHADAP KINERJA GURU SMAN SE-KOTA BEKASI - Purwani Puji Utami (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2017)
The research objective is to study the effect of the effect of work climate, job satisfaction and job dicipline toward teacher performance at Public Senior High School in Bekasi District. This research used quantitative approach. The sample of this research were 175 teachers selected randomly. The method used is survey method with path analysis. The research on the analysis it is conclude that: (1) work climate has direct effect on performance, (2) job satisfaction has direct effect on performance, (3) Job dicipline has direct effect on performance, (4) work climate has direct effect on job dicipline, (5) job satisfaction has direct effect on job dicipline, (6) work climate has direct effect on job satisfaction.